Versatile Thermochromic Supramolecular Materials Based on Competing Charge Transfer Interactions - Yuan, Tianyu; Vazquez, Mariela; Goldner, Amanda N.; Xu, Yan; Contrucci, Rafael; Firestone, Millicent A.; Olson, Mark A.; Fang, Lei (Advanced functional materials, 2016)
Stimuli‐responsive supramolecular materials are of paramount importance for a broad range of applications. It is essential to impart versatility, sustainability, and scalability into these materials. Herein the authors report the design and synthesis of a new class of thermochromic supramolecular materials, which can easily be processed from water via a reversible sol–gel transition. The supramolecular materials are composed of a bis‐bipyridinium acceptor, a π‐electron‐rich naphthalene derivative donor, and halogen counterions. Long helical nanofibers can be assembled in water, gelating at room temperature. Inked designs, thin films, and aerogels are solution‐processed to exhibit thermochromic behavior based on competing π → π* and n → π* charge transfer interactions. By using different π‐electron rich donors, and counterions, the authors demonstrate that both the color observed at room temperature and at high temperatures can be tailored. The results open up the door to develop novel amphiphile‐based thermochromes with water processability and a large tunable color palette. A new class of water‐processable thermochromic supramolecular materials has been developed. Inked designs, thin films, and aerogels fabricated from these composites exhibit reversible thermochromic behavior. The thermochromism is a result of competing π → π* and n → π* charge transfer interactions allowing for the color observed at room temperature and at high temperatures to be easily tailored.